Tracking the implementation of a risk management process in a public sector organisation – A longitudinal study. (15th October 2022) - Cedergren, Alexander; Hassel, Henrik; Tehler, Henrik
Abstract: This paper presents the results from a longitudinal study of the process of developing and implementing a method for risk assessment in a public sector organisation over a period of 3.5 years. The study explores how people involved in this process viewed factors influencing the implementation and what effects the risk management process gave rise to. While a large share of previous research on this topic has been confined to analysing the final product in terms of the documented risk assessment report, this study explores factors affecting the process leading to such outcome. Data collection was conducted through a questionnaire used on five occasions during the study period. The results from this questionnaire were complemented with an interview study to gain deeper insights and understanding of factors shaping the risk management process. The findings show a maturing process over time where the most clearly visible impact from the risk management process includes an increased risk awareness among persons involved. However, the results also indicate that the outcomes from the risk management process were only to a limited extent spread to the rest of the organisation and persons at the management level showed a declining commitment to the risk management process over the 3.5-year period. Methodologically, the paper underlines the value of adopting a longitudinal research design in the area of risk management to allow for an exploration of trends and patterns arising over time, which contributes to a deeper and more contextualised understanding of a risk management process compared to studies that only rely on capturing snapshots of an organisation's current work practices.